The Influence of Education and Training on Productive Skills, Nature of Work and Gender Inequality - GHIORGHIŢĂ, Eugen (Annals of Spiru Haret University. Economic Series, 2015)
The present paper is a synthesis of researching the evolution of gender discrimination during 2002-2013, i.e. the inclusion of women in the three levels of the national education system and the effects of education materialized in the degree of female population insertion on the labour market at national and European level. In order to grasp the still existing gender stereotypy and discrimination, it was necessary to analyze the evolution of the share of female population included in the three levels of the national education system (primary (elementary), secondary (lower and upper secondary) and tertiary (university), the correlation of the level of preparation of those graduating these three levels of the national education system with the branch structure of the employed population, respectively with the level of the average earnings (annual or monthly), at-risk-of-poverty rate by poverty threshold and education level, the identification of gender discrimination determined by gender role and gender wage disparity.